Cloud Condensation Nuclei activity in the tropical marine regions during Indian southwest monsoon. (December 2017) - Chate, D.M.; Waghmare, R.T.; Gopalakrishnan, V.; Murugavel, P.; Ghude, Sachin D.
Abstract: This paper presents the first onboard measurements of cloud condensation nuclei (CCN) distributions at super-saturations ( ss ) less than 0.5% (0.2% and 0.4%) and more than 0.5% (0.6% and 0.8%) as a function of prevailing winds during July and August over south to southeastern head-Bay region of Bay of Bengal (BoB). During monsoon season of 2012, the cross equatorial flow (CEF) along the belt 50°N–50°S was towards north and prevailing winds were stronger than normal by 2.6 ms −1 and 5.14 ms −1 respectively. Also, 2 and 5 low-pressure systems were formed during July and August 2012 respectively. Due to the strength of CEF, winds and low-pressure systems, mean value of wind speeds ( U ) observed onboard the ship during August was found to be stronger than that for July by 28%. As a result, mean values of CCN concentrations in August when winds were above 10 ms −1 were higher in magnitude by 9.5%, 15.6%, 13.4%, 12.13% and 11.9% for supersaturations of 0.2%, 0.4%, 0.6%, 0.8% and 1.0% respectively compared to corresponding means of CCN concentration during July when winds were below 10 ms −1 . Wind-driven ( U above 10 ms −1 ) CCN activity is found to be of high CCN concentrations at ss more than 0.5% despite active monsoonal cloud-aerosol interaction in the tropical marine environment. Relationships between CCN concentration and U when winds were above 10 ms −1 are found to be log10 CCN = 0.057 U + 2.4 and log10 CCN = 0.047 U + 2.6 at ss of 0.6% (R = 0.43) and 0.8% (R = 0.4) respectively, slopes of which appear to be reasonable climatic regulators for wind-induced CCN activity over south to southeastern head-Bay region of BoB. Graphical abstract: It is worth to note that during its return journey towards south at Chennai port, SK-296 cruise sailed relatively away from the southeast coastline, where prevailing air mass were with U >10 ms −1 (August 2012). For August, relationships between CCN concentrations and wind speed ( U > 10 ms −1 ) are log10 CCN = 0.057 U + 2.4 with the slope m (CCN to wind speed) of 0.057 for CCN concentrations activated at ss of 0.6%. For U > 10 ms −1 in the central Indian Ocean, shipboard measurements of Bigg, et al., (1995) suggested a relationship as log10 CCN =0.04 U +0.94 for CCN concentrations activated at ss of 0.6%. Highlights: CCN distributions are presented for a wide range of supersaturations in the marine environment of Bay of Bengal. CCN concentration increases with prevailing winds. The results are relevant to the cloud microphysics and climate change impacts.